Accelerated invasion of Nypa fruticans during 2000-2024 in degraded mangrove ecosystem in Sumatra analysed using Google Earth Engine - SYAIFUL EDDY; ANDI ARIF SETIAWAN; NORIL MILANTARA; RAHMAWATI RAHMAWATI; AZIZAN BILLARDI; AHMAD SUNDOKO (Society for Indonesian Biodiversity, 2026)
Abstract. Eddy S, Setiawan AA, Milantara N, Rahmawati, Billardi A, Sundoko A. 2026. Accelerated invasion of Nypa fruticans during 2000-2024 in degraded mangrove ecosystem in Sumatra analysed using Google Earth Engine. Biodiversitas 27 (1): d270110. https://doi.org/10.13057/biodiv/d270110. This study analyzes the invasion patterns of nipah (Nypa fruticans) and their implications for the degradation of the Air Telang Protected Forest (ATPF) ecosystem from 2000 to 2024. Using a unique methodological combination of large-scale, time-series analysis from Google Earth Engine (GEE) with high-resolution drone-based validation, we mapped land cover changes and quantified nipah expansion under intensifying anthropogenic pressures. Land cover classification from 2000, 2012, and 2024 revealed a sharp decline in native primary and secondary mangrove forests, concurrent with rapid increases in nipah-dominated areas, open lands, and plantations. This methodology allowed for a more comprehensive tracking and understanding of the invasion dynamics throughout the 2000-2024 timeframe. The Maximum Entropy algorithm was utilized to model the species' potential spread based on key environmental variables, including soil type, Normalized Difference Vegetation Index, elevation, slope, temperature, and rainfall. The results show a significant decline in native mangrove cover, directly corresponding to an increase in nipah colonies and open areas, driven by anthropogenic activities such as illegal logging and land clearing. Between 2000 and 2024, the total area of primary and secondary mangroves decreased significantly, while the invasive nipah population experienced a nearly fivefold increase. Specifically, measurements show the loss of primary mangrove forest exceeded 50% during this period. This expansion was particularly dramatic during the 2012-2024 period, marking an acceleration of the invasion. These ecological transformations not only threaten biodiversity but also substantially diminish the forest’s carbon sequestration capacity, undermining regional climate mitigation efforts. Integrated management-combining policy enforcement, restoration of native mangroves, and community-based control of nipah-is urgently needed to restore ecological function and prevent further ecosystem collapse, which provides an urgent warning for conservation policy.